Risk factors associated with changes in serum anti-Müllerian hormone levels before and after laparoscopic cystectomy for endometrioma - Zhang, Chenyu; Li, Xiaoyan; Dai, Yi; Gu, Zhiyue; Wu, Yushi; Yan, Hailan; Li, Qiutong; Shi, Jinghua; Leng, Jinhua (Frontiers in Endocrinology, 2024)
Background: The objective of our study was to investigate the risk factors for a decrease in ovarian reserve in patients with endometriomas after standardized laparoscopic procedures and evaluation to provide corresponding clinical guidance for patients with fertility requirements. Methods: Anti-Müllerian hormone (AMH) levels and other clinical data from 233 patients with endometriomas and 57 patients with non-endometrioma ovarian cysts admitted to the Peking Union Medical College Hospital between January 2018 and September 2023 were prospectively analysed. The pretreatment AMH levels of the study groups were compared to assess the impact of endometrioma on ovarian reserve, and the decrease in AMH after treatment was analysed to determine potential risk factors contributing to this change. Results: Preoperative AMH levels did not significantly differ between patients with endometriomas and those with non-endometrioma ovarian cysts. Within the endometrioma group, older age, higher body mass index (BMI), and shorter menstrual cycles were found to be associated with decreased AMH levels prior to treatment (p<0.05). The pretreatment levels of AMH exhibited a significant decline within one year in patients with bilateral cysts, advanced surgical staging, and an enclosed Douglas pouch (p<0.05). However, there was no difference in AMH levels after surgery between patients who successfully became pregnant and those who did not (p>0.05). Conclusion: Laparoscopic removal of endometriomas can adversely affect ovarian reserve, especially during bilateral cyst removal and when patients are diagnosed as having a higher stage of endometriosis, further impacting ovarian function. It should be noted that a decrease in AMH levels may not necessarily indicate an absolute decline in fertility. Therefore, it is crucial to conduct thorough patient evaluations and provide comprehensive patient education to offer appropriate guidance for fertility preservation.